COMBINATION TEST OF CHINESE LEAF EXTRACT (Leucaena leucocephala folium) AND ALOE VERA INHIBITING GROWTH Escherichia coli - Putra Rahmadea Utami; Chairani; Hendra Yudha (Universitas Nahdlatul Ulama Surabaya, 2020)
Chinese petai (Leucaena leucocephala folium) and aloe vera (Aloe vera L.) have medicinal properties among the plants. The objective of this study was to determine the number of inhibitory zones produced by the ethanol extract of Chinese petai and aloe vera on the growth of Escherichia coli. The research method was In-vitro Experimental Laboratory research design with the Kirby Bauer method. The samples used was Chinese petai and aloe vera with pure strains of E. coli. One Way ANOVA was used to compare the differences in inhibition of Chinese petai and aloe vera on the growth of E. coli. The results of a combination of Chinese petai and aloe vera extract test showed that there were significant differences in the concentration of 25 g, 50 g, 75 g, and 100 g (p <0.05). The ethanol extract of Chinese petai and aloe vera can inhibit the growth of E. coli. From the results of this study found that there was an interaction on the combination of ethanol extract of Chinese petai and aloe vera inhibiting the growth of E. coli with the most effective concentration being 100 g/mL. This study can find out the benefits of petai cina and aloe vera also the public will know the benefits and efficacy of Chinese petai and aloe vera leaves in medicine.